2022
DOI: 10.26650/ase20221131876
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic Occurrence in the Gastrointestinal Tract of a Risso’s Dolphin Grampus griseus in the Northeastern Mediterranean Sea

Abstract: Risso's dolphin Grampus griseus was stranded on the coast of Arsuz-Uluçınar, Iskenderun Bay, Turkey in the northeastern Mediterranean on 29 March 2022. This study was conducted to reveal the relationship between G. griseus and microplastic debris in the northeastern Mediterranean Sea. The gastrointestinal tract (GIT) of one stranding G. griseus was examined, and 454 microplastics particles were extracted. Of all, the majority of them were fibers (96%), black in colour (62%), and 0.5-1 mm in size (38%). This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Risso's dolphins have been reported to be seen in Fethiye (May 1995), Alanya (August 1998), Gökova (2006), Edremit (February 2007), Saros Gulf-Gelibolu (April 2011), Bodrum (May 2011), off the Mediterranean Sea (2012) (Okuş et al, 2006;Öztürk et al, 2011;Dede et al, 2013). The stranding records of Risso's dolphins off the coasts of Turkey include 2 individuals in the North Aegean between 1997-2011 (Öztürk et al, 2011), 2 individuals off Ölüdeniz in the South Aegean between 1999-2000 (Öztürk et al, 2007), 1 individual caught in fishing nets in the Mediterranean Sea (Öztürk et al, 2007;Dede et al, 2013), 1 individual in the Sea of Marmara (Dede et al, 2013) and 1 individual in the Gulf of İskenderun (Yucel et al, 2022). This study constitutes the confirmed record of G. griseus from the Northeastern Mediterranean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risso's dolphins have been reported to be seen in Fethiye (May 1995), Alanya (August 1998), Gökova (2006), Edremit (February 2007), Saros Gulf-Gelibolu (April 2011), Bodrum (May 2011), off the Mediterranean Sea (2012) (Okuş et al, 2006;Öztürk et al, 2011;Dede et al, 2013). The stranding records of Risso's dolphins off the coasts of Turkey include 2 individuals in the North Aegean between 1997-2011 (Öztürk et al, 2011), 2 individuals off Ölüdeniz in the South Aegean between 1999-2000 (Öztürk et al, 2007), 1 individual caught in fishing nets in the Mediterranean Sea (Öztürk et al, 2007;Dede et al, 2013), 1 individual in the Sea of Marmara (Dede et al, 2013) and 1 individual in the Gulf of İskenderun (Yucel et al, 2022). This study constitutes the confirmed record of G. griseus from the Northeastern Mediterranean.…”
Section: Discussionmentioning
confidence: 99%
“…Risso's dolphins are reported to be distributed in the Mediterranean Sea from the Alboran Sea to the Aegean Sea (Luna et al, 2022).In the Turkish Seas, Risso's dolphins were reported to be seen in Fethiye (May 1995), Alanya (August 1998), Gökova (2006), Edremit (February 2007), Saros Gulf-Gallipoli (April 2011), Bodrum (May 2011), off the Mediterranean coast of Turkey (2012) (Okuş et al, 2006;Öztürk et al, 2011;Dede et al, 2013). The stranding records of Risso's dolphins off the Turkish coasts were reported as 2 individuals in the North Aegean between 1997 and 2011 (Öztürk et al, 2011), 2 individuals off Ölüdeniz in the South Aegean between 1999 and 2000 (Öztürk et al, 2007), 1 individual caught in a fishing net in the Mediterranean Sea (Öztürk et al, 2007; 2011 see Dede et al, 2013), 1 individual in the Marmara Sea (Dede et al, 2013) and 1 individual in İskenderun Bay (Yucel et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Cetaceans interact with microplastics through direct ingestion from the environment or through trophic transfer. Although there are several studies available for other regions [ 25 , 26 , 27 , 28 , 29 , 30 ], in the Black Sea, the topic is still largely unexplored. The lack of information is mostly attributed to limited research endeavours.…”
Section: Introductionmentioning
confidence: 99%